Progressive sperm motility is associated with spontaneous pregnancy after varicocelectomy (Faculty of Medicine Universitas Indonesia, 2018)
Background: Varicocelectomy is performed on patients with clinical varicocele associated with abnormal sperm parameters. The goal of this procedure is to improve men's sperm parameters and pregnancy rates of their partners. The objective of our study was to assess the factors that were associated with spontaneous pregnancy in female partners after varicocelectomy.Methods: A retrospective case-control study was conducted to review several factors that are associated with spontaneous pregnancy after varicocelectomy. The data were taken from medical records at Sanglah General Hospital and three private hospitals in Denpasar from January 2015 to June 2016. Case subjects (n=38) include varicocele patients with abnormal sperm parameters whose partner had a spontaneous pregnancy following varicocelectomy and a control group (n=38) whose partner did not have a spontaneous pregnancy following varicocelectomy.Results: Progressive sperm motility (≥37.5%) before varicocelectomy was 2.7 times more likely to result in a spontaneous pregnancy (odds ratio: 2.7; 95% confidence interval: 1.04–6.96; p=0.04). No statistical significance was found between age at varicocelectomy, grade of varicocele, body mass index, infertility duration, smoking habit, sperm concentration, normal sperm morphology before varicocelectomy, and spontaneous pregnancy.Conclusion: Progressive sperm motility before varicocelectomy is a significant factor for the occurrence of spontaneous pregnancy after varicocelectomy.